The Apoptotic, Angiogenic and Cell Proliferation Genes CD63, S100A6 e GNB2L1 are Altered in Patients with Endometriosis - Valéria Aguiar Gomes; Camila de Moraes Bonocher; Júlio César Rosa-e-Silva; Cláudia Cristina Paro de Paz; Rui Alberto Ferriani; Juliana Meola (Revista Brasileira de Ginecologia e Obstetrícia, 2018)
Abstract Objective The aim of the present study was to analyze the expression of the CD63, S100A6, and GNB2L1genes, which participate in mechanisms related to the complex pathophysiology of endometriosis. Methods A case-control study was conducted with 40 women who were diagnosed with endometriosis, and 15 fertile and healthy women. Paired samples of eutopic endometrium and endometriotic lesions (peritoneal and ovarian endometriotic implants) were obtained from the women with endometriosis in the proliferative (n = 20) or secretory phases (n = 20) of the menstrual cycle. As controls, paired endometrial biopsy samples were collected from the healthy women in the proliferative (n = 15) and secretory (n = 15) phases of the samemenstrual cycle.We analyzed the expression levels of the CD63, S100A6, and GNB2L1 genes by real-time polymerase chain reaction. Results An increase in CD63, S100A6, and GNB2L1 gene transcript levels was observed in the ectopic implants compared with the eutopic endometrium of the women with and without endometriosis, regardless of the phase of the menstrual cycle. Conclusion These findings suggest that the CD63, S100A6, and GNB2L1 genesmay be involved in the pathogenesis of endometriosis, since they participate in mechanisms such as inhibition of apoptosis, angiogenesis and cell proliferation, which lead to the loss of cell homeostasis in the ectopic endometrium, thus contributing to the implantation and survival of the tissue in the extrauterine environment.